Development of Voltammetry Analysis Method of Iron Metal Ions by Solid-State Membrane with Carbon Nanotube - Suyanta, Suyanta; Sunarto, Sunarto; Padmaningrum, Regina Tutik; Karlinda, Karlinda; Isa, Illyas Md; Zainul, Rahadian; Fardiyah, Qonitah; Kurniawan, Fredy (Universitas Gadjah Mada, 2024)
This work developed a selectively modified electrode for measuring the Fe(II) ions in continuous integration using voltammetry techniques. The study assessed various aspects, such as linearity, scan rate, repeatability, and real sample analysis. The experiment is performed using differential pulse voltammetry (DPV). The findings of the study indicated that the voltammetry method exhibited a regression line of y = 36.507 ln(x) + 990.73, with a correlation value of 0.9627, with an optimum scan rate of 20 mV/s and good repeatability over five times measurement. On the other hand, when comparing the results using the UV-Vis spectrophotometric technique, the regression equation was found to be y = 0.20438x − 0.06987, with a correlation value of 0.99583. Notably, the voltammetry measurement outperformed the UV-Vis method since it allowed analysis of Fe(II) at concentrations up to 6.35 × 10−4 ppm (or 1.00 × 10−11 M), while the UV-vis measurement could only analyze up to 1.5 ppm (or 2.36 × 10−5 M). Consequently, the developed technique proves to be superior to the other methods for the analysis of Fe(II).